CARACTERIZACIÓN BIOQUÍMICA PARCIAL DE PROTEÍNAS ALERGIÉNICAS DE FRAXINUS SINENSIS Y CECROPIA SP. - Rodríguez, Adriana; Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
The allergenic capabilities ofthe poli en of Fraxinus sinensis (Urapán) and Cecropia sp. (Y arumo) were determined in patients with respiratory allergies in the city ofBogotá. Of a total of207 patients wbo were subjected to therelevant allergy skin tests, 20 (9.66%) were positive for F. sinensis and 6 (2.9%) for the extract from Cecropia sp. The allergenicity was confirmed by the determination of specific Iinmunoglobulin E (lgE). Of the twenty patients positive for F. sinensis, only 6 ofthem allowed fora blood test, and5 oftheseshowed a positive reaction to the extract. The bands mainly detected by IgE, using immunodetection after separation by SDS-PAGE and IEF, had molecular weights of95 and 64 kd and IP's of 6.3 and 5.6. When compared to other allergenic proteins according to their crossreactivity, the extract from Olea europaea was found to contain a bigher concentration of relevant allergens than the extracts from F. vlilutina, F. pennsylvanica, F. latifolia and F. mericana. Dueto the small number of serum samples obtained from allergic patients, it is not possible todo an allergogram for the pollen extract of Fraxinus sinensis. As for Cecropia, none of the in vitro tests that were done showed positive resultS, wbich makes it impossible to draw relevant conclusions. These results demonstrate the need of more research that characterizes the allergens peculiar to our atrnosphere in order to optimize the diagnosis and treatrnent of allergy patients in Colombia